Improving Ways to Raise Earthquake Sustainability of the Individual Buildings in Uzbekistan - Ikromjon ugli, Jalilov Ahmadbek (European Journal of Life Safety and Stability (2660-9630), 2022)
As more than 63.7% of the population of Uzbekistan (about 24 million people) live in seismic zones with a magnitude of 8-9, their lives and health are at risk in emergencies associated with a strong earthquake (greater than 5). Construction of earthquake-resistant buildings and structures is one of the important tasks in order to reduce risks and minimize losses [13]. Unfortunately, the principles of earthquake resistance are currently being grossly violated in the construction of most private houses (individual buildings). Even simple dimensional and design requirements for seismicity remain unfulfilled. Therefore, because they are not earthquake-resistant, they are severely damaged during a strong earthquake, and even some are highly likely to be completely destroyed. The consequences of strong earthquakes in the second half of the XX century and the first twenty years of the XXI century in the territory of Uzbekistan are a clear evidence of this. In this regard, it is important to assess and ensure the seismic safety of low-rise buildings made of local materials, to develop methods to increase their strength in seismically active zones of the Republic of Uzbekistan